THE SIGNIFICATORS OF OBLIGATION IN THE POLISH AND SPANISH CIVIL CODES - NOWAK-MICHALSKA, Joanna (Comparative Legilinguistics, 2013)
In this paper the significators (i. e. linguistic indicators) of one of the deontic meanings, viz. obligation, in the Polish and Spanish civil codes are presented and compared. The significators of obligation which can be words (classified according to the part of speech they belong to) or syntagms, were identified as a result of an analisis of the corpus. Also, the contex of a normative text (here: statutory instruments) can be the only significator of obligation in a sentence which appeared in such a text. In order to provide a more precise description, the significators are classified according to the semantic category of the word which is the subject of the sentence where the significator appeared. It is also indicated whether a significator is used in the present or future tense.